2011
DOI: 10.1029/2011jd016343
|View full text |Cite
|
Sign up to set email alerts
|

Fine and ultrafine particles at a near–free tropospheric environment over the high-altitude station Hanle in the Trans-Himalaya: New particle formation and size distribution

Abstract: [1] Number-size distributions of ultrafine, fine, and accumulation mode aerosols in the size range 5-1300 nm have been measured regularly from the pristine, high-altitude (for 4520 m above mean sea level) station Hanle in the Trans-Himalaya during the summer and autumn (August-November) 2009. The total number concentration ranged from 80 to 8000 cm −3 with a mean value of 1150 cm −3. Examination of the temporal variations of the size distributions indicated that formation of new ultrafine particles from the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…This observatory is also a part of the network of observatories under Aerosol Radiative Forcing over India (ARFI) project of ISRO-GBP, which is now known as ARFINET 23,24 . Some of the findings from this observatory have been published earlier [25][26][27][28][29][30][31] . These include the role of photochemistry in the new particle formation events at the freetropospheric altitudes 25 , temporal evolution and annual cycle in BC concentration over the Himalaya 26 , dust transport and associated changes in physical and optical properties of aerosols [27][28][29][30][31] and spring-time enhancement in aerosol optical depth (AOD) and BC over Hanle 30 .…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…This observatory is also a part of the network of observatories under Aerosol Radiative Forcing over India (ARFI) project of ISRO-GBP, which is now known as ARFINET 23,24 . Some of the findings from this observatory have been published earlier [25][26][27][28][29][30][31] . These include the role of photochemistry in the new particle formation events at the freetropospheric altitudes 25 , temporal evolution and annual cycle in BC concentration over the Himalaya 26 , dust transport and associated changes in physical and optical properties of aerosols [27][28][29][30][31] and spring-time enhancement in aerosol optical depth (AOD) and BC over Hanle 30 .…”
Section: Introductionmentioning
confidence: 85%
“…Some of the findings from this observatory have been published earlier [25][26][27][28][29][30][31] . These include the role of photochemistry in the new particle formation events at the freetropospheric altitudes 25 , temporal evolution and annual cycle in BC concentration over the Himalaya 26 , dust transport and associated changes in physical and optical properties of aerosols [27][28][29][30][31] and spring-time enhancement in aerosol optical depth (AOD) and BC over Hanle 30 . While these earlier works are focused on characterization of aerosol optical and physical properties over Hanle, this article presents the quantitative estimation of spring-time enhancement in aerosol loading, its vertical structure and possible reasons for the inter-annual variability in springtime enhancement based on long-term observations of aerosol properties over Hanle during August 2009-December 2014.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In sharp contrast, Hanle (32.78 • N, 78.96 • E; 4520 m a.m.s.l) is an extra-tropical high-altitude, nearpristine location in the western trans-Himalayas and southwest of the Tibetan plateau (Verma et al, 2009;Moorthy et al, 2011;Babu et al, 2011). Measurements were made from a mountaintop observatory, ∼ 300 m above the surrounding sparsely populated valley region.…”
Section: Methodsmentioning
confidence: 99%
“…While high-altitude locations at free tropospheric heights, which act as reservoirs for several gaseous species, witness NPF events on the synoptic scale through gas-particle conversion under favourable conditions, such as the availability of abundant UV radiation and moisture (Weber et al, 1995(Weber et al, , 1999Weingartner et al, 1999;Shaw, 2007;Nishita et al, 2007;Moorthy et al, 2011), urban and coastal environments have been observed to be potentially important sources of highly intense but localised aerosol formation bursts (O'Dowd et al, 1998a(O'Dowd et al, , b, 1999(O'Dowd et al, , 2002bVäkevä et al, 2000;Stanier et al, 2004;Ahlm et al, 2012) where abundant availability of moisture and volatile gases (anthropogenic, biogenic, and urban activities) exists. Distinctiveness in growth dynamics for these various environmental conditions is worth investigating.…”
Section: Introductionmentioning
confidence: 99%